Perancangan Promosi Produk Aphrodites.Core Melalui Aplikasi Shopee - Selindion Tembesi selin; Mikke R. Marentek; Wingston Markus J. Londong; Nancy Henrietta Jessamine Mandey (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
The importance of designing appropriate and effective promotions for businesses so that businesses can be recognized and influence increased marketing and business actors can meet market share. Every business can develop its products and special markets by implementing appropriate promotion and marketing systems. The aim of this research is to design promotions for Aphrodites Core accessory products and add online platforms as promotional media. To achieve this goal, researchers used descriptive quantitative methods, through collecting observational data on the media used by business actors and designing promotional media for Aphrodites Core products. The research results add to the Market Place platform that business actors can use to become a promotional medium and provide a separate role for business actors in carrying out online promotions. One of the goals of designing the Shopee application is as a promotional media so that Aphrodite Core accessory products are known among the wider community, as well as creating promotional media with several displays.